2018
DOI: 10.3390/ijms20010055
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Colla corii asini against Lung Injuries Induced by Intratracheal Instillation of Artificial Fine Particles in Rats

Abstract: Environmental issues pose huge threats to public health, particularly the damage caused by fine particulate matter (PM2.5). However, the mechanisms of injury require further investigation and medical materials that can protect the lungs from PM2.5 are needed. We have found that Colla corii asini, a traditional Chinese medicine that has long been used to treat various ailments, is a good candidate to serve this purpose. To understand the mechanisms of PM2.5-induced lung toxicity and the protective effects of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…However, such studies are often limited by challenges when it comes to determining exact exposure doses and the variances associated with large population studies, and this makes it difficult to perform mechanistic studies or draw clear mechanistic conclusions (Brook et al, 2010;Yang et al, 2016). Laboratory studies of PM indeed revealed molecular mechanisms of PM-induced toxicities, but most studies used PM particles that were collected and washed from filters (Kundu and Stone, 2014;Liu T. et al, 2018) and exposed animals with either intratracheal instillation or inhalation chambers (Chen et al, 2013;Pardo et al, 2015). Loss of the water-soluble partition of the PMs and relatively high doses of exposure over a short period of time decreased the relevancy of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies are often limited by challenges when it comes to determining exact exposure doses and the variances associated with large population studies, and this makes it difficult to perform mechanistic studies or draw clear mechanistic conclusions (Brook et al, 2010;Yang et al, 2016). Laboratory studies of PM indeed revealed molecular mechanisms of PM-induced toxicities, but most studies used PM particles that were collected and washed from filters (Kundu and Stone, 2014;Liu T. et al, 2018) and exposed animals with either intratracheal instillation or inhalation chambers (Chen et al, 2013;Pardo et al, 2015). Loss of the water-soluble partition of the PMs and relatively high doses of exposure over a short period of time decreased the relevancy of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Subvermispora was applied for Pinus taeda wood chips bioprocessing in solid-state fermentation, the lignin of which was mainly degraded by the β-O-aryl ether cleavage by the MnP and laccase [ 36 ]. The laccase ( Lcc1 ) isolated from Ganoderma tsugae can promote lignin decomposition, mycelium growth, pigment formation, and stipe elongation [ 37 ]. The lignin degradation property of white-rot fungi makes it useful in the biopulping process of paper industry.…”
Section: Lignin Depolymerization By Microorganisms and Enzymesmentioning
confidence: 99%
“…8−11 Environmental issues pose huge threats to public health, particularly the damage caused by small-diameter PM. 12−16 Short-term or long-term exposure to PM instigates adverse health effects upon the cardiovascular (CV) system 17 and cancer. 14 Diesel particulate filtering (DPF) are considered one of the most efficient technologies in removing diesel engine PM.…”
Section: Introductionmentioning
confidence: 99%
“…), particulate matter (PM) (dry soot smoke, soluble organic fraction, ash, sulfate, etc. ), , carbon monoxide, and unburned hydrocarbons. Environmental issues pose huge threats to public health, particularly the damage caused by small-diameter PM. Short-term or long-term exposure to PM instigates adverse health effects upon the cardiovascular (CV) system and cancer …”
Section: Introductionmentioning
confidence: 99%